BEYOND LEGALITY: REFRAMING ABUSE OF AUTHORITY THROUGH THE LENS OF UTILITY AND ACCOUNTABILITY IN ADMINISTRATIVE LAW - Ade Rachmad Hidayat; Shexy Intan Pratama Sari; Cholidah Utama (Taksasila Edukasi Insani, 2026)
The increasing prevalence of authority abuse in public administration highlights the inadequacy of legality-based oversight systems in ensuring just and accountable governance. This study aims to reframe the understanding of administrative authority by integrating the principles of legality, utility, and accountability within the context of administrative law. Employing a qualitative design with doctrinal analysis, comparative case studies, and semi-structured interviews involving public officials, oversight bodies, and scholars, the research explores how these principles interact to prevent and evaluate abuse of authority. The findings reveal that administrative control in Indonesia remains heavily procedural, resulting in a persistent utility gap and accountability gap where decisions may be lawful but lack measurable public benefit. The study introduces a new conceptual framework Administrative Accountability Based on Utility which positions public value creation as a central criterion for legitimate authority. This model contributes theoretically by extending administrative justice beyond legality toward functional and ethical governance. Practically, it proposes institutional reforms such as impact-based audits and outcome-oriented accountability mechanisms. The research concludes that administrative legitimacy must derive not only from rule compliance but also from demonstrable social utility and answerability, paving the way for more responsible and value-driven governance systems.Keywords: accountability, administrative law, authority abuse, public value, utility